Tea for histamine anti-allergy: component analysis of tea extracts and potential mechanism for treating histamine anti-allergy - Huang, Zeting; Zhang, Lanyue; Xuan, Jie; Yang, Lu; Zhao, Tiantian; Peng, Weihua (Frontiers in Pharmacology, 2024)
In China, Camellia plants are widely used to reduce atopic dermatitis and inflammation-related diseases, but their protective mechanisms remain unclear. This study investigated the anti-allergic dermatitis, anti-oxidation and anti-inflammation effect and underlying mechanism of five Camellia species, including Camellia ptilophylla Chang, C. assamica Chang var. Kucha Chang, C. parvisepala Chang, C. arborescens Chang, and C. assamica M. Chang. A total of about 110 chemical compositions were detected from five Camellia teas extracts. The level of mast cell infiltration in the model mice skin was determined by HE (Hematoxylin and eosin) staining and toluidine blue staining, and the level of interleukin-1β (IL-1β) and nerve growth factor (NGF) was detected by immunohistochemistry. The five Camellia tea leaf extracts have histamine-induced allergic dermatitis. Lipopolysaccharide (LPS)induced murine macrophage RAW264.7 inflammation model was found to secrete NF-κB factor, asshown by immunofluorescence, and reactive oxygen species (ROS) secretion and related cytokine levels were detected. The results suggested that Camellia's five tea extracts had the ability to resist cellular oxidative stress. In addition, the results of cell inflammatory cytokines including fibronectin (FN) and interleukin-6 (IL-6) suggested that the five tea extracts of Camellia had anti-inflammatory effects. Therefore, it is suggested that five Camellia teas may possess inhibitory properties against allergic reactions, oxidative stress, and inflammation, and may prove beneficial in the treatment of allergies.